Feeding level and frequency for freshwater angelfish - Ribeiro, Felipe de Azevedo Silva; Vasquez, Leonardo Avendaño [UNESP]; Fernandes, João Batista Kochenborger [UNESP]; Sakomura, Nilva Kazue [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to determine the optimal feeding level and feeding frequency for the culture of freshwater angelfish (Pterophyllum scalare). A randomized block design in a factorial scheme (3 × 2) with three feeding levels (30, 60 and 90 g/kg of body weight (BW)/day) and two feeding frequencies (1x and 2x/day) was set up in duplicate, representing 24 experimental units. Data were analyzed using two-way ANOVA and the Tukey test for comparison between means. After 84 days, results indicated that both factors influenced fish performance. No interaction between these factors was, however, observed. Increased feeding level and feeding frequency resulted in increased feed intake. The feed conversion ratio was negatively affected by feeding level, but not affected by feeding frequency. Final weights were higher when fish were fed twice daily, at levels of 60 or 90 g/kg BW/day. Specific growth rate was higher when fish received 60 or 90 g/kg BW/day, regardless of the feeding frequency. Survival was not affected by any treatment, with mean survival rates higher than 90%. It is recommended that juveniles be fed at a level of 60 g/kg BW/day with a minimum of two meals per day, to attain optimal survival, growth and feed efficiency.
Keywords: aquarium fish; feed conversion rate; feed intake; nutrition; ornamental fish; specific growth rate